Using GeoGebra as a tool for better understanding of geometrical shapes and concepts - Talokar, Nitin (Voices of Teachers and Teacher Educators, 2015)
This article explores the use of GeoGebra, a dynamic mathematics software, as an educational tool to enhance the understanding of geometrical shapes and concepts. GeoGebra allows users to visualize and interact with geometric objects, providing a hands-on learning experience that bridges the gap between abstract mathematical theory and practical application. By enabling students to manipulate shapes, explore properties, and experiment with transformations in real-time, GeoGebra fosters a deeper comprehension of geometric relationships, theorems, and constructions. The article examines various features of GeoGebra, such as interactive diagrams, 3D modeling, and algebraic representations, and discusses how these tools can be effectively integrated into classroom instruction. Case studies and examples are provided to demonstrate how GeoGebra can be used to teach key geometric concepts, from basic shapes to more complex topics like conic sections and transformations. The article concludes by emphasizing the potential of GeoGebra to support a more engaging and intuitive approach to learning geometry, catering to diverse learning styles and improving student outcomes.